AGAMA DAN SEKSUALITAS PEREMPUAN - Nawangsari (Al'Adalah, 2013)
The Qur'an explicitly confirms the equality of men and women, though Muslim communities in general do not view men and women equal. Even humiliation against women often happens, as a result of the authoritarian understanding of the religious messages. As a result, the products of Islamic thought often positions women as subordinate, or the second class. This fact is certainly very alarming, therefore religious doctrines and fatwas with discriminatory practices, must be re-examined if it is to Islam remains a mercy to all the worlds.